Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025926
|View full text |Cite
|
Sign up to set email alerts
|

Self-Confidence Trumps Knowledge

Abstract: Computer security tools usually provide universal solutions without taking user characteristics (origin, income level, ...) into account. In this paper, we test the validity of using such universal security defenses, with a particular focus on culture. We apply the previously proposed Security Behavior Intentions Scale (SeBIS) to 3,500 participants from seven countries. We first translate the scale into seven languages while preserving its reliability and structure validity. We then build a regression model to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Language is a part of the culture. Previous cross-cultural studies (Halevi et al , 2016; Sawaya et al , 2017) have found the difference in security behaviour. This study also found the influence of mother tongue and, in turn, culture on cybersecurity behaviours and practices.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Language is a part of the culture. Previous cross-cultural studies (Halevi et al , 2016; Sawaya et al , 2017) have found the difference in security behaviour. This study also found the influence of mother tongue and, in turn, culture on cybersecurity behaviours and practices.…”
Section: Discussionmentioning
confidence: 77%
“…Mother tongue-based hypothesis : Asian users are likely not to use phone locking mechanism and are more likely to exhibit insecure behaviour than users from other cultures (Sawaya et al , 2017). India was ruled out from earlier such studies because of the multiplicity of different local languages.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, existing literature has conducted cross-national ISA research, which discovered that more secure cybersecurity behaviour was, to some extent, related to a country's higher GDP or better development, while the results were constantly changing. [42,43].…”
Section: Isa In Uencing Factorsmentioning
confidence: 99%
“…Several studies have been conducted to analyze how the cultural differences are correlated with user behavior or attitude toward security. Harbach et al [8] and Sawaya et al [9] conducted user-based surveys in multiple countries. To this end, these two research groups attempted to translate their survey questions into the participants' native languages.…”
Section: Cross-cultural User Surveys On Securitymentioning
confidence: 99%
“…Harbach et al [8] aimed at investigating user attitude toward smartphone unlocking and they found that the level of protection of smartphone data was significantly different among various countries and Japanese participants tended to consider that their data on their smartphone is sensitive. Sawaya et al [9] recruited participants from seven countries, i.e., China, France, Japan, Korea, Russia, the United Arab Emirates, and the United States. They investigated security behavior and various other factors such as security knowledge and self-confidence in security, and concluded that Asian participants, especially Japanese, tended to behave less securely.…”
Section: Cross-cultural User Surveys On Securitymentioning
confidence: 99%